Panoramic video coding based on spherical distortion with spatio-temporal dependency - Xu YANG; Ce ZHU; Hongwei GUO; Lei LUO (Tongxin xuebao)
The planar coding distortion, which affects objective quality, and spherical distortion, which affects subjective quality, as well as existing independent rate-distortion optimization techniques that fail to consider the temporal propagation of spherical distortion and its impact on coding performance, result in coding performance degradation.To address these issues, a spatio-temporal dependent spherical distortion model was proposed for optimizing panoramic video coding.Firstly, a spatial mapping model was proposed to map spherical distortions to coding distortions, aiming to align subjective and objective quality assessments.Secondly, a temporal propagation model for spherical distortions was introduced to enhance the overall coding performance of all coding units in the propagation chain.Finally, the coding parameters were adjusted by computing the weights for spatial mapping and temporal propagation of spherical distortions.Experimental results demonstrate that, under low-delay encoding configurations, compared to the VTM14.0, a state-of-the-art video coding benchmark, the proposed algorithm achieves an average bitrate savings of 7.4% (up to 22.1%) and reduction in coding time of 9%.